Investigating the influence of zinc oxide nanoparticles on the pathogenesis of lung fibrosis - Lee, Melissa Kao Hui (Nanyang Technological University, 2023)
Indoor air pollution is widely recognized as a threat to public health and is a particularly pressing issue in manufacturing workplaces which are exposed to unhealthy levels of airborne hazards. Zinc oxide nanoparticles (ZnO NPs) are among the growing scale of environmental risk factors released during the manufacturing process, with potential to induce detrimental effects on human health. To date, there have been numerous studies done on the direct ZnO NP-induced cytotoxic response, which exert a variety of cellular effects such as adaptation, oxidative stress, genotoxicity, intracellular organelle dysfunction and apoptosis. However, studies on the ZnO NP-induced effects via alterations to cell-cell signaling remain scant, particularly in disease development and progression. In this study, ZnO NPs (<100 nm) were employed to investigate the NP-induced intracellular changes and paracrine signaling events in the epithelial-interstitium microenvironment contributing to the pathogenesis of lung fibrosis. Here, Calu-3 bronchial epithelial cells were treated with varying doses of ZnO NPs, and cell viability, oxidative stress and barrier permeability were assessed. In addition, the conditioned medium of ZnO NP-treated Calu-3 cells were added to human lung fibroblast culture, and expression of myofibroblast marker alpha smooth muscle-actin was evaluated. A strong pro-fibrotic influence was observed at both the gene and protein level in lung fibroblasts using conditioned medium from Calu-3 cells treated with a high dose of ZnO NPs. Further investigations into the ZnO NP-induced signaling changes were carried out via RNA-Sequencing analysis of ZnO NP-treated Calu-3 cells, and the pro-fibrotic phenomenon observed was attributed mainly to the increase in pro-inflammatory cytokine expression, with C-X-C motif Chemokine Ligand 8 (CXCL8) being identified as a potential critical mediator of the Calu-3 paracrine signaling response. Overall, the treatment of ZnO NPs led to a variety of dose-dependent effects whereby an increase in cytotoxicity, oxidative stress and pro-fibrotic stimulation was observed with increasing ZnO NP dosage. Taken together, this study provides critical insights into the safety of ZnO NPs in the context of inhalation and respiratory diseases.